2021
DOI: 10.1038/s41380-021-01129-7
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity ultrasound restores long-term potentiation and memory in senescent mice through pleiotropic mechanisms including NMDAR signaling

Abstract: Advanced physiological aging is associated with impaired cognitive performance and the inability to induce long-term potentiation (LTP), an electrophysiological correlate of memory. Here, we demonstrate in the physiologically aged, senescent mouse brain that scanning ultrasound combined with microbubbles (SUS+MB), by transiently opening the blood–brain barrier, fully restores LTP induction in the dentate gyrus of the hippocampus. Intriguingly, SUS treatment without microbubbles (SUSonly), i.e., without the upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 54 publications
(75 reference statements)
4
29
1
Order By: Relevance
“…Hence, FUS neuromodulation of the dorsal striatum without BBB opening may have qualitatively different effects that FUS-mediated BBB opening. This is in contrast to the results of a recent study in senescent mice [53] in which FUS was directed to the dentate gyrus of the hippocampus with and without BBB opening. In that study, BBB opening after FUS with microbubbles led to recovery of long-term potentiation (LTP).…”
Section: Discussioncontrasting
confidence: 99%
“…Hence, FUS neuromodulation of the dorsal striatum without BBB opening may have qualitatively different effects that FUS-mediated BBB opening. This is in contrast to the results of a recent study in senescent mice [53] in which FUS was directed to the dentate gyrus of the hippocampus with and without BBB opening. In that study, BBB opening after FUS with microbubbles led to recovery of long-term potentiation (LTP).…”
Section: Discussioncontrasting
confidence: 99%
“…We therefore used 20-22 month-old WT mice to determine whether therapeutic ultrasound can restore cognitive functions in the aged mouse brain. We made the remarkable observation that six weekly sessions of either SUS +MB or, surprisingly, SUS only , restored LTP induction in these aged mice [11] (Figure 1). This demonstrates that in the physiologically aged brain, BBB opening, i.e., blood-borne factors entering the brain, is not required for the observed restorative effects of SUS.…”
Section: Therapeutic Improvements In Senescent Mice Using Therapeutic Ultrasoundmentioning
confidence: 86%
“…Physiological ageing leads to a progressive decline in the functional and cellular constituents of the brain [19]. In a recent study, we explored the neuromodulatory potential of SUS in aged, cognitively impaired C57BL/6 wild-type mice [11]. Earlier studies in the lab in wild-type mice applied SUS +MB and were intended to assess short-and long-term safety.…”
Section: Therapeutic Improvements In Senescent Mice Using Therapeutic Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Blackmore et al corroborated these findings in a recent study that showed FUS restored long-term potentiation and memory in senescent mice. Specifically, they demonstrated that FUS significantly raised levels of TRPA1 levels in synaptosomal hippocampal fractions compared with sham treatments [ 94 ]. This increase, reflected by the changes observed for NMDAR subunits in these fractions, suggests that ultrasound-mediated astrocytic glutamate release is a likely mechanism by which FUS led to the observed improvements in senescent mice, which may also explain the improvements in locomotor behaviour as seen in PD models [ 94 ].…”
Section: Discussionmentioning
confidence: 99%